Effect of Gamma Irradiation on Mechanical and Thermal Properties of Fish Gelatin Film Isolated from Lates Calcarifer Scales - Dian Pribadi Perkasa; Erizal Erizal; Darmawan Darmawan; Akhmad Rasyid (Indonesian Journal of Chemistry, 2013)
The objective of this research was to investigate the effect of gamma irradiation on mechanical and thermal properties of fish gelatin films prepared from scales of Lates calcarifer. The films were irradiated by gamma rays at varied doses (0-50 kGy). The mechanical and thermal properties of irradiated gelatin films were measured by using colorimeter, Universal Testing Machine, Differential Scanning Calorimetry (DSC), and Fourier Transform Infrared (FTIR) spectrophotometer. The results showed that increasing of irradiation dose up to 50 kGy, the color of irradiated film did not change significantly (p < 0.05). The tensile strength of irradiated film was increased with no differences among dose variation but there was no change on elongation at break value (p < 0.05). The DSC spectra of irradiated gelatin films showed that irradiation did not affect melting temperature (Tm). In contrast, the glass transition temperature (Tg) of irradiated film has slight tendency to increase with increasing of radiation doses. In general, the FTIR spectra confirmed that gamma irradiation up to 50 kGy affected the mechanical properties of gelatin films.